Thin section petrography, geochemistry and scanning electron microscopy of archaeological ceramics - Quinn, Patrick S. ca. 20./21. Jh (Archaeopress, 2022)
Using over 400 colour figures of a diverse range of artefact types and archaeological periods from 50 countries worldwide, this book outlines the mineralogical, chemical and microstructural composition of ancient ceramics and provides comprehensive guidelines for their scientific study within archaeology
Keywords: Keramik; Archäometrie